'Where your mama at?' Observations from the fishbowl: thoughts and experiences on working at a community pre-school. Issue 2 (3rd May 2016) - Deletant, Rowena
Abstract : This paper chronicles my time working in the American South, in a pre-school for deprived children, aged from two to four years old. The experience highlights the situations of these children and explores the environment within which they develop. This raises many questions about the unconscious processes which are possibly at work and how trauma affects the capabilities and capacities of those involved in their care. The paper gives an overview of the societal context before focusing on the individual children's experience, and the impact of this on the staff. The author uses her subjective observations to hypothesise an understanding of the inner experience for the other. She reflects on the impact and value that child psychotherapists might bring to this environment.